(untitled) (Comparatismi, 2016)
Though identity and narrative are the subjects of many discussions, the two terms are not usually accompanied by any adjective, as if identity necessarily meant “rigid identity”, and narrative were synonymous of “linear, coherent narrative” (in the most reductive acceptation of coherence). Quite the contrary, it is necessary to rediscover the polysemy of the concept of identity, linking narrative theory to philosophies and theories of the subject. Identity exists only in its modes and in the conflict between coincidence and non-coincidence.